ANALISIS PEMANFAATAN MANAJEMEN STRATEGIS MENGGUNAKAN ANALISIS SWOT PADA PT. PARAHYANGAN GOLF BANDUNG - Zidan Syafiq Ramadhan; Yani Iriani (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2022)
This research was conducted at the Parahyangan Golf Club in Bandung. The purpose of this study was to determine the appropriateness of marketing strategy management based on the level of suitability of the increase and decrease in visitors at Parahyangan Golf Bandung. Currently, golf is increasingly in demand by foreign and domestic tourists. Golf is also used as one of the main programs of tourists who carry out convention events and is used as a competition or tournament. The competition that occurs is very tight between one golf course and another. conducted at Parahyangan Golf Bandung. Based on the results of this study, the results obtained showed an increase and decrease in visitors every month caused by several factors affecting visitors and marketing strategies